2018
DOI: 10.1186/s13613-018-0472-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect on comfort of administering bubble-humidified or dry oxygen: the Oxyrea non-inferiority randomized study

Abstract: BackgroundThe clinical interest of using bubble humidification of oxygen remains controversial. This study was designed to further explore whether delivering dry oxygen instead of bubble-moistened oxygen had an impact on discomfort of ICU patients.MethodsThis randomized multicenter non-inferiority open trial included patients admitted in intensive care unit and receiving oxygen. Any patient receiving non-humidified oxygen (between 0 and 15 L/min) for less than 2 h could participate in the study. Randomization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
8
1
1
Order By: Relevance
“…Furthermore, the patient had no history of use of anticoagulants or antiplatelet drugs before the onset of the sudden epistaxis, this reports contrast the observation from another study were most of the patients who had spontaneous epistaxis reported taking anticoagulants or antiplatelet prior to the onset of COVID-19 [16]. Also of note, all the patient in the aforementioned study had a risk factor of use of non-humidified oxygen therapy during their stay in the hospital, this factors have been implicated as a major cause of spontaneous epistaxis in other studies [17][18][19]. This report further adds to the fact that COVID-19 is a novel disease that still needs further population survey to clearly highlight all its clinical features.…”
Section: Case Presentationcontrasting
confidence: 52%
“…Furthermore, the patient had no history of use of anticoagulants or antiplatelet drugs before the onset of the sudden epistaxis, this reports contrast the observation from another study were most of the patients who had spontaneous epistaxis reported taking anticoagulants or antiplatelet prior to the onset of COVID-19 [16]. Also of note, all the patient in the aforementioned study had a risk factor of use of non-humidified oxygen therapy during their stay in the hospital, this factors have been implicated as a major cause of spontaneous epistaxis in other studies [17][18][19]. This report further adds to the fact that COVID-19 is a novel disease that still needs further population survey to clearly highlight all its clinical features.…”
Section: Case Presentationcontrasting
confidence: 52%
“…All of our patients were receiving non-humidified oxygen either via a low-flow nasal cannula or continuous positive expiratory pressure via a helmet. Such treatments are known risk factors for nasal dryness, 6 8 and prolonged oxygenation will increase the risk of crust formation, which will then weaken the nasal mucosa and expose the patient to an increased risk of nasal bleeding. A second risk factor in this specific population is the use of anticoagulant drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Poiroux et al, 2018 67 Standard oxygen via NC or simple face mask with humidification Mortality, escalation of care, and subjects complications were not statistically different between humidified and nonhumidified cohorts.…”
Section: In Adult Patients Managed Postopera-mentioning
confidence: 95%
“…Even given the above evidence, studies have not been able to determine that nonhumidified supplemental oxygen is inferior to humidified supplemental oxygen. Poiroux et al 67 studied humidified and nonhumidified oxygen delivered via nasal cannula at various flows. They reported that nonhumidified oxygen at flows > 4 L/min may be associated with higher levels of discomfort but, overall, oxygen therapy-related discomfort was low.…”
Section: Humidification Of Oxygenmentioning
confidence: 99%